Lipid Nanomaterials for Targeted Delivery of Dermocosmetic Ingredients: Advances in Photoprotection and Skin Anti-Aging - Souto, Eliana B.; Jäger, Eliézer; Jäger, Alessandro; Štěpánek, Petr; Cano, Amanda; Viseras, Cesar; Barbosa, Raquel de Melo; Chorilli, Marlus [UNESP]; Zielińska, Aleksandra; Severino, Patricia; Naveros, Beatriz C. (MDPI, 2022)
Despite the health benefits of the sun, overexposure to solar radiation without proper precautions can cause irreversible damage to exposed skin. In the search for balance between the risks and benefits of exposure to solar radiation in human health, a technological alternative was found, the incorporation of photoprotective products in lipid nanoparticulate systems for topical application. These nanometric systems have demonstrated several advantages when used as adjuvants in photoprotection compared to chemical and/or physical sunscreens alone. The increase in the sun protection factor (SPF), photostability and UV action spectrum are parameters that have benefited from the application of these systems in order to increase the effectiveness and safety of photoprotective formulations containing organic and/or inorganic sunscreens.
Keywords: Lipid nanofilms; Solar photoprotection; sun exposure; Ultraviolet radiation